Transformasi Tata Kelola SDM Menuju Pelayanan Profesional Pada Teman Nginap Hospitality Yogyakarta - Debora Wintriarsi handoko; Daniel Yudistya Wardhana; Nadia Nila Sari; Endang Raino Wirjono (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The rapid growth of the tourism sector in the Special Region of Yogyakarta has not yet been fully matched by managerial readiness in the hospitality MSME sector. Teman Nginap Yogyakarta MSMEs are one example of partners facing challenges in human resource (HR) management and organizational structure. This community service program aims to optimize HR management through a participatory-interactive mentoring approach. The program was implemented through six main stages, combining two approaches: academic education (fundamentals of HRM and job analysis) and practitioner-led training (best practices in recruitment, training/on-the-job training, and performance evaluation systems). The final evaluation results showed a very high level of satisfaction among the partner’s management. This mentoring program successfully provided new perspectives and transformed operational processes to be more structured, efficient, and professional, thereby ensuring long-term business sustainability.